2015
DOI: 10.1186/s12885-015-1396-5
|View full text |Cite
|
Sign up to set email alerts
|

How do we estimate survival? External validation of a tool for survival estimation in patients with metastatic bone disease—decision analysis and comparison of three international patient populations

Abstract: BackgroundWe recently developed a clinical decision support tool, capable of estimating the likelihood of survival at 3 and 12 months following surgery for patients with operable skeletal metastases. After making it publicly available on www.PATHFx.org, we attempted to externally validate it using independent, international data.MethodsWe collected data from patients treated at 13 Italian orthopaedic oncology referral centers between 2010 and 2013, then applied to PATHFx, which generated a probability of survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 30 publications
4
56
0
1
Order By: Relevance
“…On external validation, discriminatory ability of the 1-and 6-month models was similar to those previously studied [6,11]. Specifically, the 3-month and 12-month models contained in PATHFx showed AUCs of 0.79 and 0.76, respectively, when confronted with this external validation data set and DCA showed that both of these models were suitable for use in the Scandinavian patient population [6].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…On external validation, discriminatory ability of the 1-and 6-month models was similar to those previously studied [6,11]. Specifically, the 3-month and 12-month models contained in PATHFx showed AUCs of 0.79 and 0.76, respectively, when confronted with this external validation data set and DCA showed that both of these models were suitable for use in the Scandinavian patient population [6].…”
Section: Discussionsupporting
confidence: 75%
“…If surgeons are unsure regarding whether an estimate is appropriate, he or she should select ''unknown.'' Doing so will maintain accuracy of the model, while not introducing undue bias, as shown in two prior external validation studies [6,11].…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations